ASSESSMENT OF OPTIMAL OSMOTIC PRESSURE OF CITRATE EGG YOLK EXTENDER FOR CRYOPRESERVATION OF BUFFALO BULL (B UBALUS BUBALIS) - SEMEN D. H. Mughal; A. Ijaz; M. S. Yousaf; H. Rehman; M. Aleem; H. Zaneb; F. Wadood (Journal of Animal and Plant Sciences, 2013)
The study was designed to assess the effects and optimal range of osmotic pressure of citrate egg yolk extender (CEYE) for cryopreservation of buffalo bull semen. Semen samples of four Nili-Ravi buffalo bulls, kept for artificial insemination (AI) purposes, were collected at weekly interval for five weeks. Five solutions of tri-sodium citrate dihydrate and D (-) fructose of varying osmotic pressures (255, 265, 275, 285 and 295 mOsm/kg) were used to prepare citrate egg yolk extender. The semen samples were frozen at -196°C using 20 x 106spermatozoa/0.5ml straw. The postthaw evaluation was carried out in terms of spermatozoa motility, viability, acrosomal integrity, plasma membrane integrity (PMI), spermatozoa DNA integrity and lipid peroxidation. The buffalo bull spermatozoa motility was significantly (P<0.05) affected by varying osmotic pressures and the spermatozoa were more motile (50.3 ± 4.2 %) in the semen samples extended with CEYE at an osmotic pressure of 295 mOsm/kg compared to 275, 265 and 255 mOsm/kg. Other spermatozoa characteristics including viability, acrosomal integrity, PMI, DNA integrity and lipid peroxidation were remained same in all the treatments groups. The osmotic pressure of 285-295 mOsm/kg was considered to be most suitable for most of the spermatozoa characteristics for the cryopreservation of buffalo bull semen.
Keywords: Nili Ravi; semen quality; osmotic pressure; citrate extender; cryopreservation